2010
DOI: 10.1002/jcb.22495
|View full text |Cite
|
Sign up to set email alerts
|

Breviscapine protects against cardiac hypertrophy through blocking PKC‐α‐dependent signaling

Abstract: Breviscapine is a mixture of flavonoid glycosides extracted from the Chinese herbs. Previous studies have shown that breviscapine possesses comprehensive pharmacological functions. However, very little is known about whether breviscapine have protective role on cardiac hypertrophy. The aim of the present study was to determine whether breviscapine attenuates cardiac hypertrophy induced by angiotensin II (Ang II) in cultured neonatal rat cardiac myocytes in vitro and pressure-overload-induced cardiac hypertroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Previous studies have demonstrated that breviscapine ameliorated cardiac hypertrophy that was induced by high glucose or angiotensin II. Studies have also reported that breviscapine had a protective effect against diabetic cardiomyopathy in diabetic rats [15][16][17] . However, little is known about whether breviscapine has a protective role in diabetic atherosclerosis, which is a common complication of diabetes mellitus that is independent of diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous studies have demonstrated that breviscapine ameliorated cardiac hypertrophy that was induced by high glucose or angiotensin II. Studies have also reported that breviscapine had a protective effect against diabetic cardiomyopathy in diabetic rats [15][16][17] . However, little is known about whether breviscapine has a protective role in diabetic atherosclerosis, which is a common complication of diabetes mellitus that is independent of diabetic cardiomyopathy.…”
Section: Discussionmentioning
confidence: 92%
“…A number of reports have demonstrated that breviscapine possessed a strong inhibitory effect on PKC-α and PKC-β2 activation that contributed to its protective roles in cerebral ischemia, hepatic injury during brain death and cardiac hypertrophy [13,[15][16][17]33] . To investigate whether the protective effect of breviscapine on VSMCs is related to PKC, PKC-β2 activation was evaluated in VSMCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the C57BL/6 mice were allocated at random into four groups: Sham + naringenin, AB + naringenin, sham + vehicle and AB + vehicle (n=15 per group). AB was performed as described previously (11). At 8 weeks after surgery, the animals were euthanized by cervical dislocation while anesthetized with 1.5% isoflurane, and the hearts were dissected and weighed to calculate the heart weight/body weight (HW/BW, in mg/g), heart weight/tibia length (HW/TL, in mg/mm) and lung weight/body weight (LW/BW, in mg/g) ratios in the naringenin-treated and vehicle-treated mice.…”
Section: Methodsmentioning
confidence: 99%
“…Then, hearts were cut transversely [20,21]. Sections were examined by light microscopy for lesions and changes in myofiber thickness or arrangement (H&E, ×200) and the myocyte cross sectional area was quantitatively analyzed with NIH Image 1.61 software as previously described (H&E, ×400) [6,18].…”
Section: Histomorphologymentioning
confidence: 99%